Simulating effect of parameter variation on the performance of an educational system. (2018) - Messaoudi, Najat; Naciri, Jaafar Khalid; Bensassi, Bahloul
The present study proposes a first model simulating the effect of variations of a group of parameters on the global performance of an educational system. To achieve the simulation, each training cycle of the educational system is broken down into different levels. The training unit is defined as the lower component of this decomposition. A generic processor is selected for modelling each training unit. A mathematical model enabling simulation of the increase of learner's competence based on a production function is proposed. This function relates the increase of competencies of each learner to a set of parameters such as the time dependency, the class size, the personal capacity of each learner. The obtained curves clearly show the relationship between performance, variation in the number of learners and sensitivity of the pedagogical method. Simulations over the effect of group homogeneity on the performance versus class size curves are presented.